Effect of Wheat Flour Substitution with Quinoa Flour Fortified with Turmeric Powderon Fish Nugget Properties - Sakamut, Phatthira; Sompongse, Warangkana (Thai Journal of Science and Technology, 2022)
The objective of this study was to develop a batter with the minimal possibility of wheat flour replacement with quinoa flour and fortification with turmeric powder. The investigation of the effect of wheat flour substitution with quinoa flour (50-100%) and the optimum of turmeric powder (5-15%) in fried batter on physical and chemical properties of fish nuggets was studied. The results showed that the increasing substitution level of quinoa flour exhibited higher viscosity of batter, but lower values of L* and b* in fried batter (p<0.05), as compared to control (0%). The cooking loss value and the textural characteristics of the sample with quinoa flour-blended fried batter at 50% were not significantly different from that of the control (p>0.05). Therefore, quinoa flour-blended fried batter at 50% substitution was selected to further investigate the optimum of turmeric powder level in fried batter. The resulted presented that the hardness, gumminess and chewiness increased as the turmeric powder level increased (p<0.05). The sample with turmeric powder-blended fried batter showed significantly lower L* value in fried batter and whiteness in mince, but higher in cooking loss, compared to the control. No significantly different was found in viscosity between sample with turmeric powder-blended fried batter at 5% and control (p>0.05). At this level, the lipid oxidation value of sample was decreased by 7.94% and the DPPH radical scavenging percentage was increased by 36.87%.